2018
DOI: 10.1002/path.5164
|View full text |Cite
|
Sign up to set email alerts
|

HMGA2 promotes intestinal tumorigenesis by facilitating MDM2‐mediated ubiquitination and degradation of p53

Abstract: High mobility group A2 (HMGA2) is an architectural transcription factor that promotes human colorectal cancer (CRC) aggressiveness by modulating the transcription of target genes. The degradation of p53 is mediated by murine double minute 2 (MDM2) in a proteasome-dependent manner. Here we report that HMGA2 promotes cell cycle progression and inhibits apoptosis in CRC cells in vitro. We also developed an intestinal epithelial cell-specific Hmga2 knock-in (KI) mouse model. It revealed that the Hmga2 KI promoted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 47 publications
1
22
0
Order By: Relevance
“…Studies have shown that HMGA2 has effects in cancer development via regulating various signaling pathways, such as MDM2/p53, IL11/STAT3, and Wnt/β-catenin pathways ( Fig. 1 ) [ 40 , [46] , [47] , [48] , [49] ].
Fig.
…”
Section: Hmga2 and Colorectal Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that HMGA2 has effects in cancer development via regulating various signaling pathways, such as MDM2/p53, IL11/STAT3, and Wnt/β-catenin pathways ( Fig. 1 ) [ 40 , [46] , [47] , [48] , [49] ].
Fig.
…”
Section: Hmga2 and Colorectal Cancermentioning
confidence: 99%
“…Deletion mapping studies demonstrated that the two (amino acids 1–73) or three AT-hook domains (amino acids 1–83) of HMGA2 and the central acidic and zinc finger domains of MDM2 (amino acids 111–360) were sufficient for their association. Our findings indicated that HMGA2 directly interacted with p53 and MDM2, thereby increasing MDM2-mediated p53 ubiquitination and subsequently decreasing p53 protein stability and expression [ 46 ].…”
Section: Hmga2 and Colorectal Cancermentioning
confidence: 99%
“…Many proteins have been found to regulate p53 stability by affecting the interaction between p53 and MDM2. For example, LACTB stabilizes the p53 protein by disrupting the p53-MDM2 interaction 9 ; HMGA2 directly interacts with both p53 and MDM2 to enhance MDM2-mediated p53 ubiquitination and degradation 11 .…”
Section: Introductionmentioning
confidence: 99%
“… 10 , 11 , 12 , 13 Chromosomal translocations with breakpoints in HMGA2 that eliminate the 3’ UTR let-7 miRNA binding sites cause multiple tumor types. 36 , 37 , 38 High expression of HMGA2 in cancers of epithelial origin associates with increased aggressiveness 39 , 40 and is seen in some leukemias. 41 Chromosomal translocation of HMGA2 has also been seen in two cases of paroxysmal nocturnal hemoglobinuria.…”
Section: Discussionmentioning
confidence: 99%